Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada CV Sukses Bersama Stationery Jakarta Utara - Levina Meileny Anis Tintia; Retno Japanis Permatasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Study This aim For know influence in a way simultaneous between motivation and discipline Work to performance employees at CV Sukses Bersama Stationery, North Jakarta. Method used is associative quantitative . Population study as many as 60 people in total become sample in study This . Data analysis techniques used is an instrument test , an assumption test classic , analysis descriptive , regression test , coefficient test correlation , coefficient test determination and hypothesis testing . Research result show that motivation and discipline Work in a way Partial influential to performance employee amounted to 37.6% whereas the remaining 62.4% is influenced by other variables that are not researched . Discipline Work in a way Partial influential to performance employee amounted to 63.1% whereas the remaining 36.9% is influenced by other variables that are not researched . Motivation and discipline Work in a way simultaneous influential to performance employee amounted to 70.5% whereas the remaining 29.5% is influenced by other variables that are not researched . Research result show equality multiple linear regression Y = 2.775 + 0.284 X1 + 0.641 Simultaneously motivation and work discipline have a positive and significant effect on employee performance, this is proven by the calculated F value > F table, namely (68.272 > 3.16) with a significance of 0.000 < 0.05, so H0 is rejected and H3 is accepted, meaning there is an influence positive and significant relationship between motivation and work discipline on employee performance simultaneously at CV Sukses Bersama Stationery, North Jakarta.